Verum Corpus : La presencia eucarística en el diálogo Anglicano-Católico Romano - Blanco Sarto, Pablo (Dialogo ecumenico, 2019)
In these lines we address what has been called the punctum dolens of the theological dialogue on the Eucharist between Anglicans and Catholics. The question of the real presence is mentioned again and again in the ecumenical documents, trying to face the Anglican condemnation of the doctrine of transubstantiation. We therefore analyze this particular topic in the official Anglican - Roman Catholic dialogue along the different documents that emerged from Vatican II. Finally we finish the present study to this difficult topic with an approach to two Cambridge women (Ascombe, Pickstock), which perhaps offer new hope in the dialogue about the nature of the presence of Jesus Christ in the Eucharist.